CONTRIBUTION OF CHARCOAL ANALYSIS TO THE STUDY OF VEGETAL PALEOENVIRONMENT IN CATALONIA (SPAIN) - MORA, M T R (BULLETIN DE LA SOCIETE BOTANIQUE DE FRANCE-ACTUALITES BOTANIQUES, 1992)
Charcoal analysis of seventeen archaeological sites in Catalonia (north-east of Spain) gives an approach to the Holocenic vegetation history for this area. We establish four regionals patterns for the vegetation evolution : interior non continental, north-mediterranean, south-mediterranean and interior continental. We also notice the effects of anthropic action and the ancient distribution of particular species : Olea europeae, Fagus sylvatica, Pinus halepensis, Quercus suber.
Keywords: CHARCOAL ANALYSIS; REGIONAL PATERNS; vegetation history